Drinking patterns at the sub-national level: What do they tell us about drinking cultures in European countries?. Issue 4 (August 2017) - Bloomfield, Kim; Grittner, Ulrike; Kraus, Ludwig; Piontek, Daniela
Aim: A drinking pattern is not only a major drinking variable, but is also one indicator of a country's drinking culture. In the present study, we examine drinking patterns within and across the neighbouring countries of Denmark and Germany. The aim of the research is to determine to what extent drinking patterns differ or are shared at the sub-national level in the two countries. Method: Data came from the German 2012 Epidemiological Survey of Substance Use ( n = 9084) 18–64 years (response rate 54%), and the Centre for Alcohol and Drug Research's 2011 Danish national survey ( n = 5133) 15–79 years (response rate 64%), which was reduced to a common age range, producing a final n = 4016. The drinking pattern variable included abstention, moderate drinking, heavy drinking, risky single occasion drinking (RSOD), and was investigated with bivariate statistics and gender-specific hierarchical cluster analysis. Results: For men three clusters emerged: one highlighting abstention and RSOD, moderate/heavy drinking, RSOD and RSOD + heavy drinking. For women, two clusters appeared: one highlighting abstention and moderate/heavy drinking and the other highlighting RSOD and RSDO + heavy drinking. The clusters revealed different geographical patterning: for men, a west vs. east divide; for women, a north–south gradient. Conclusions: The analysis could identify for each gender clusters representing both separate and shared drinking patterns as well as distinctive geographical placements. This new knowledge can contribute to a new understanding of the dynamics of drinking cultures and could indicate new approaches to prevention efforts and policy initiatives.